ANXIETY AMONG NON-HEALTH WORKERS DURING THE COVID-19 PANDEMIC: A CROSS SECTIONAL ONLINE STUDY IN INDONESIA - Idaiani, Sri; Yulianto, Aris; Wirasmi, Sundari; Herawati, Maria Holly; Massie, Roy GA; Mubasyiroh, Rofingatul; Suryaputri, Indri Yunita; Indrawati, Lely; Sitorus, Nikson; Isfandari, Siti; Nurkhotimah, Enung (Malaysian Journal of Public Health Medicine, 2024)
The COVID-19 pandemic has an impact on all populations, including non-health workers. As the pandemic's trajectory remains uncertain, holistic, inclusive, and multidisciplinary, interventions become paramount. Therefore, this study aims to determine the anxiety level among non-health workers and its influential determinants. Participants were workers from the Ministry of Health in Indonesia. The on-line anxiety questionnaire used was the General Anxiety Disorder Questionnaire 7 (GAD-7). Data analysis was carried out using the STATA statistical program, and 1020 participant responses were analyzed. The proportion of non-health workers experiencing anxiety during the COVID-19 pandemic was as follows: 26.7% (95% CI=24.03-29.47) experienced mild anxiety; 4.60% (95% CI=3.48-6.08) experienced moderate anxiety; and 1.76% (95% CI=1.11-2.78) experienced severe anxiety, while 66.90% (95% CI= 64.0-69.80) of respondents did not report anxiety. Furthermore, it was observed that having more than one chronic illness was the most contributing factor to anxiety (OR adj= 1.838 (95% CI=1.063 - 3.178)); p = 0.029. Unsurprisingly, it was found that the anxiety of non-health workers is lower than that of health care workers in Indonesia. In addition, the risk of experiencing anxiety is higher among workers with more than one chronic disease. A suggestion that can be made is that non-health workers must continue to control their health even during the pandemic.